Increasing sustainability and reproducibility of in vitro toxicology applications: serum-free cultivation of HepG2 cells - Pfeifer, Luisa Marie; Sensbach, Janike; Pipp, Frederic; Werkmann, Daniela; Hewitt, Philip (Frontiers in Toxicology, 2024)
Fetal Bovine Serum (FBS) is an important ingredient in cell culture media and the current standard for most cells in vitro. However, the use of FBS is controversial for several reasons, including ethical concerns, political, and societal pressure, as well as scientific problems due to the undefined and variable nature of FBS. Nevertheless, scientists hesitate to change the paradigm without solid data de-risking the switch of their assays to alternatives. In this study, HepG2 cells, a human hepatoblastoma cell line commonly used to study drug hepatotoxicity, were adapted to serum-free conditions by using different commercially available media and FBS replacements. After transition to these new culture conditions, the success of adaptation was determined based on cell morphology and growth characteristics. Long-term culturing capacity for each medium was defined as the number of passages HepG2 cells could be cultured without any alterations in morphology or growth behavior. Two media (Advanced DMEM/F12 from ThermoFisher and TCM® Serum Replacement from MP Biomedicals) showed a long-term cultivation capacity comparable to media containing FBS and were selected for further analysis. Both media can be characterized as serum-free, however still contain animal-derived components: bovine serum albumin (both media) and bovine transferrin (only TCM® serum replacement). To assess the functionality of the cells cultivated in either of the two media, HepG2 cells were treated with reference compounds, specifically selected for their known hepatotoxicity characteristics in man. Different toxicological assays focusing on viability, mitochondrial toxicity, oxidative stress, and intracellular drug response were performed. Throughout the different assays, response to reference compounds was comparable, with a slightly higher sensitivity of serum-free cultivated HepG2 cells when assessing viability/cell death and a lower sensitivity towards oxidative stress. Taken together, the two selected media were shown to support growth, morphology, and function of serum-free cultivated HepG2 cells in the early preclinical safety space. Therefore, these results can serve as a starting point to further optimize culture conditions with the goal to remove any remaining animal-derived components.